2022
DOI: 10.1177/15563316221096675
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT for Preoperative Assessment of Lumbar Degenerative Spondylolisthesis: The Unique Impact of L4 Bone Mineral Density on Single-Level Disease

Abstract: Background: Quantitative computed tomography (qCT) efficiently measures 3-dimensional vertebral bone mineral density (BMD), but its utility in measuring BMD at various vertebral levels in patients with lumbar degenerative spondylolisthesis (LDS) is unclear. Purpose: We sought to determine whether qCT could differentiate BMD at different levels of LDS, particularly at L4-L5, the most common single level for LDS. In addition, we sought to describe patterns of BMD for single-level and multiple-level LDS. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…One study found the supine lateral radiograph captured more reduction in anterolisthesis than did the extension radiograph, 16 and another study found the combination of upright lateral radiograph and supine magnetic resonance imaging (MRI) was better at identifying LDS than flexion-extension radiographs. 15 Computed tomography (CT) scans, which can be used for additional operative considerations such as quantitative CT for bone mineral density, 17 presumably would be similarly effectively in imaging displacement in the supine position and therefore also may be useful for comparisons. Finally, comparison of fluoroscopic images done in the operating room at the time of surgery may be most reliable in delineating the extent of displacement.…”
mentioning
confidence: 99%
“…One study found the supine lateral radiograph captured more reduction in anterolisthesis than did the extension radiograph, 16 and another study found the combination of upright lateral radiograph and supine magnetic resonance imaging (MRI) was better at identifying LDS than flexion-extension radiographs. 15 Computed tomography (CT) scans, which can be used for additional operative considerations such as quantitative CT for bone mineral density, 17 presumably would be similarly effectively in imaging displacement in the supine position and therefore also may be useful for comparisons. Finally, comparison of fluoroscopic images done in the operating room at the time of surgery may be most reliable in delineating the extent of displacement.…”
mentioning
confidence: 99%